Perfectionism in Children and Adolescents with Eating-Related Symptoms: A Systematic Review and a Meta-Analysis of Effect Estimates - Audrey Livet; Xavier Navarri; Philippe Pétrin Pomerleau; Sébastien Champagne; Fakir Md Yunus; Nicholas Chadi; Gail McVey; Patricia Conrod (MDPI AG, 2023)
Background: Over 40 years of research implicates perfectionism in eating disorders in childhood and adolescence. However, the nature of this relationship remains understudied. To address this gap, we performed a systematic review and a meta-analysis to quantify the magnitude of the associations between perfectionism (i.e., unidimensional perfectionism, perfectionistic strivings, and perfectionistic concerns) and eating-related symptoms during childhood and adolescence. Methods: The literature search was conducted using five electronic databases in accordance with PRISMA guidelines: MEDLINE, Embase, CINAHL Complete, APA PsycINFO, and EMB Reviews. A total of 904 studies were identified; a total of 126 were included in the systematic review, and 65 in the meta-analysis (N = 29,268). Sensitivity analyses were also carried out to detect potential differences in age and clinical status. Results: All the associations we investigated were both significant and positive. Small effect sizes were found between eating global scores and unidimensional perfectionism, perfectionistic strivings, and perfectionistic concerns (res = 0.19, res = 0.21, res = 0.12, respectively) and remained significant in each age group in both clinical and community samples. Perfectionistic concerns were moderately associated with all eating measures, especially in community samples and samples with a mean age under 14. Conclusions: Psychological interventions specially designed to target perfectionistic concerns in the early stages of development may help prevent the onset or reduce the intensity of eating-related symptoms during childhood and adolescence.